Efficient synthesis method of CsPbBr3/Al2O3 composite powders for scalable production: Augmented green emission and thermal stability - Kim, Seok Hun; Shin, Weon Ho; Oh, Jong Min; Kim, Sang Wook; Kim, Sunghoon (Journal of Industrial and Engineering Chemistry, 2025)
Metal halide perovskites (MHPs) have gained significant attention for their exceptional optoelectronic properties, particularly in displays. However, their practical utility is severely limited by their intrinsic instability, including poor thermal stability, photostability, and susceptibility to moisture-induced degradation. This study introduces scalable synthesis of CsPbBr3/Al2O3 green-emitting phosphors, using submicron Al2O3 as a support, comparing mechanochemical reaction (MRM) and dissolution-evaporation (DEM) methods. DEM is the optimal route, enabling the formation of monoclinic CsPbBr3/Al2O3 with high photoluminescence quantum yield (PLQY) and enhanced stability. The influence of the CsPbBr3 to Al2O3 mass ratio on PLQY was quantitatively analyzed using the Halder-Wagner method, which indirectly calculated crystallite size and its correlation with PLQY. The composite demonstrated exceptional thermal stability, maintaining over 90 % of its initial PL intensity after 200 °C exposure for 15 days and showed excellent photostability, maintaining nearly its initial luminous efficiency under the currents of 20 mA and 70 mA for 10000-seconds. When integrated as a green phosphor in a white LED package with K2SiF6:Mn+4 as a red phosphor, it achieved a luminous efficiency of 25 lm W−1 and a color gamut of 112.4 % NTSC. These results highlight the potential of CsPbBr3/Al2O3 composites for cost-effective, stable, and high-performance optoelectronic applications.
Keywords: Cspbbr3/al2O3 composite; Dissolution-evaporation method; Efficient synthesis; Evaporation method; Green-emitting phosphors; Luminous efficiency; Photo-stability; Photoluminescence quantum yields; Synthesis method; Thermal; CsPbBr3/Al2O3 composite; Dissolution-evaporation method; Green-emitting phosphor; Photostability; Thermostability